Interaksi Antagonistik antara Lactobacillus 5ns dan Candida tropicalis - H., Julistiono; Hardiansyah, R.; Yulinery, T.; Napitupulu, R.N.R. (Perhimpunan Biologi Indonesia, 2001)
ABSTRACTAntagonistic Interaction between Lactobacillus 5NS and Candida tropicalis. Centrifuged supernatant of medium where Lactobacillus 5NS grown inhibited growth of three strains of Candida tropicalis. The Inhibition activity was detected using paper disc method. When the supernatant was induced with living cells of C. tropicalis Y393 strain, it inhibited the tested yeast strains. Inhibition activities of this supernatant against C. tropicalis Y390, Y391 and Y393 were equivalent to that of phenol at the concentration of 20.56 , 25.02 and 25.04 mg/ml, respectively. However when the supernatant was induced with heated or living cells of Candida tropicalis Y390 and Y391, it did not show any inhibition activity on all yeast strain tested. Thus the data indicates that there may be a specific interaction between Lactobacillus 5NS and C. tropicalis Y393 in which under the induction of specific certain yeast such as C. tropicalis Y393, Lactobacillus 5NS produces a toxin-like that is not spesific for the yeast target. Such interaction between normal flora and patogenic yeast may be happen in the digestive tractus.Key words: Lactobacillus, yeast, Candida tropicalis, antagonist